Islam and Democracy: The Case of the Early Reform Era - Abdillah, Masykuri (JURNAL INDO-ISLAMIKA, 2024)
Almost all ulama and Muslim intellectuals in Indonesia accept the term “democracy” and support it as a system that must be implemented in Indonesia. The emergence of the “reform era” following the fall of authoritarian Soeharto’s government in 1998 was marked as the starting point of the transition to substantive democracy. The political reform took the form of conducting free elections, developing a multiparty system, and guaranteeing more freedom for the press and citizens to express their opinions and criticism, and the amendments to the 1945 Constitution. This ran well, so the democratic transition was considered successful. The political parties and civil society organizations, including those with an Islamic background, played an important role in this transition. To develop a civilized democracy in Indonesia, the government, political parties, and civil societies, especially religious organizations, made efforts to strengthen ethics and moral education as well as civic education, conveying values in a democratic system, such as tolerance, trust, responsibility, law consciousness, and others. This research was done through qualitative approach, based on library documents.